2013
DOI: 10.1001/jamainternmed.2013.836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Creative Arts Therapies on Psychological Symptoms and Quality of Life in Patients With Cancer

Abstract: Importance: Creative arts therapies (CATs) can reduce anxiety, depression, pain, and fatigue and increase quality of life (QOL) in patients with cancer. However, no systematic review of randomized clinical trials (RCTs) examining the effects of CAT on psychological symptoms among cancer patients has been conducted.Objectives: To estimate the effect of CAT on psychological symptoms and QOL in cancer patients during treatment and follow-up and to determine whether the effect varied according to patient, interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 83 publications
4
76
0
1
Order By: Relevance
“…The other 34 systematic reviews were about psychosocial interventions [15, 16, 22, 38, 42, 44, 45], massage therapy [17, 21, 24, 33, 46], acupuncture [18, 35, 36, 41, 43], reflexology [23, 30, 32], Chinese herbal medicine [20, 40, 48], music therapy [31, 39], transcutaneous electric nerve stimulation [37], cupping [34], cannabis [27], lycopene [25], Viscum album L (European Mistletoe) [29], Reiki [28], homeopathic therapy (Traumeel) [19], creative arts therapies [47], and internal qigong [26]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other 34 systematic reviews were about psychosocial interventions [15, 16, 22, 38, 42, 44, 45], massage therapy [17, 21, 24, 33, 46], acupuncture [18, 35, 36, 41, 43], reflexology [23, 30, 32], Chinese herbal medicine [20, 40, 48], music therapy [31, 39], transcutaneous electric nerve stimulation [37], cupping [34], cannabis [27], lycopene [25], Viscum album L (European Mistletoe) [29], Reiki [28], homeopathic therapy (Traumeel) [19], creative arts therapies [47], and internal qigong [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Six systematic reviews [7, 17, 31, 35, 37, 45] have “a priori” design, four systematic reviews [26, 31, 36, 39] conducted duplicate data extraction, six systematic reviews [17, 22, 38, 40, 43, 45] conducted duplicate study selection, 25 systematic reviews [7, 15–18, 21, 2326, 2935, 37, 40, 4247] have comprehensive literature search, all systematic reviews provided a list of studies (included and excluded), 24 systematic reviews [15–17, 1921, 24, 2628, 3032, 3537, 39, 40, 4246, 48] provided the characteristics of the included studies, and five systematic reviews [27, 30, 31, 33, 39] assessed and documented the scientific quality of the included studies. The other details of quality were presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Les activités créatives (par exemple l'écriture et les arts visuels comme la peinture) sont associées à une diminution des symptômes de dépression, de stress et de fatigue, tout en améliorant le bien-être chez les patients atteints de cancer (Haltiwanger, Rojo et Funk, 2011;Visser et Op'T Hoog, 2008). Une revue systématique d'essais cliniques aléatoires et de différentes activités d'art-thérapie ayant porté sur 1 576 patients cancéreux (total de 27 études) a révélé une diminution de l'anxiété, de la dépression et de la douleur, ainsi qu'une amélioration moyenne à élevée de la qualité de vie (Puetz, Morley et Herring, 2013). Même si cette revue de littérature démontre l'efficacité d'une approche axée sur les arts, la plupart des devis de recherche utilisés dans ces études n'ont utilisé qu'une seule intervention, soit la musicothérapie.…”
Section: Introductionunclassified
“…Creative processes (e.g., writing, and visual arts such as painting) have also been shown to reduce symptoms of depression, stress and fatigue, while enhancing well-being in cancer patients (Haltiwanger, Rojo, & Funk, 2011;Visser & Op'T Hoog, 2008). A systematic review of RCTs and various creative arts therapies found reduced anxiety, depression, and pain, as well as improved quality of life (QOL) with medium to large effect sizes across 27 studies involving 1,576 cancer patients (Puetz, Morley, & Herring, 2013). While this review demonstrates the effectiveness of arts-based approaches, most of the studies utilized music therapy, indicating that writing is understudied.…”
mentioning
confidence: 99%